Financial Performance Analysis of MSMEs Using KUR (People Business Credit) Funds Before and During the Covid-19 Pandemic - Sigalingging, Mega Setia Mawarni; Darmansyah, Asep (Journal of Business and Management, 2020)
Abstract. Pandemic Covid-19 is predicted by the IMF to bring world finances worse than the 2007-2008 crisis to -3% in 2020. KUR (People's Business Credit) is a government program in supporting MSMEs as a contributor to GDP in Indonesia, especially in the capital. However, this pandemic significantly affects the sustainability of MSMEs, especially in the Doloksanggul sub-district. This study will conduct a financial ratio analysis between before and during a pandemic to see the weaknesses of MSMEs, which can help restore Indonesia's finances. The analysis carried out with three ratios: solvency, activity, and profitability, to three business sectors: trade, production, and services. Based on the results of the analysis, for MSMEs engaged in trade, especially those who sell gas, the solvency ratio decreases while the ratio of activity and profitability increases. For production businesses, those producing snacks and services, namely tailors, experience the opposite of business in trade. In solvency has increased, and the ratio of activity and profitability has decreased. It can conclude that the trade sector experienced excellent financial performance while other businesses did not.Keywords: MSMEs, KUR (People Business Credit), Financial Ratio Analysis.